Adaptive Dialogic Digital Parenting and Screen Time Regulation in Indonesian Early Childhood Families: An Explanatory Sequential Mixed Methods Study - Asmawulan, Tri; Katoningsih, Sri; Kunca Az Zahra, Ichita; Wafa, Khadijah; Diaz Aziz Pramudita (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
Children’s encounters with digital media have intensified debate on how families regulate screen exposure while sustaining its educational, social, and relational value. Although screen time and parental mediation have been widely examined, less is known about how regulation is enacted in collectivist family ecologies where parents, grandparents, siblings, and caregivers may share authority over children’s daily routines. This study examined the association between digital parenting mediation and screen time regulation among Indonesian families with children aged 4 to 6 years. Using an explanatory sequential mixed methods design, data were collected from 30 purposively selected parents at Al Fajar Juwiring Kindergarten through a 24-item questionnaire, semi-structured interviews, home observations, and documentation review. Quantitative data were analysed descriptively and through Pearson correlation, while qualitative data were analysed thematically and integrated through connected and merged interpretation. The findings show that active mediation, content selection, consistent rule communication, and parental involvement were associated with children’s screen time regulation. The strongest association was found between consistency and parental control and children’s regulation behaviour (r = .701, p < .001), indicating that predictable boundaries supported by warm explanation were more meaningful than restriction alone. Qualitative findings revealed responsive mediation, negotiated household regulation, meaningful non-digital substitution, and emotional accompaniment as key mechanisms for managing transitions away from screens. The study contributes to international family media mediation scholarship by proposing adaptive dialogic digital parenting as a culturally situated framework for understanding how stable rules, responsive communication, parental modelling, and intergenerational coordination support children’s digital habits and emerging self-regulation.